Cover Picture: Perchlorination of Coronene Enhances its Propensity for Self‐Assembly on Graphene (ChemPhysChem 3/2016). Issue 3 (4th February 2016) - Conti, Simone; del Rosso, Maria G.; Ciesielski, Artur; Weippert, Jürgen; Böttcher, Artur; Shin, Yuyoung; Melinte, Georgian; Ersen, Ovidiu; Casiraghi, Cinzia; Feng, Xinliang; Müllen, Klaus; Kappes, Manfred M.; et al.
Abstract : Perchlorination of coronene significantly enhances its propensity to form a self‐assembled monolayer at the liquid–graphene interface. More information can be found in the Communication by M. M. Kappes, P. Samorì, M. Cecchini et al. onpage 352 in Issue 3, 2016 (DOI:10.1002/cphc.201501113 ).